Comparison of the Effectiveness of Resilient Dialectical Behavior Therapy and Dialectical Behavior Therapy on Sense of Coherence and Marital Interactions in Women with Marital Burnout - Shirani Nezhvani, Maryam; Khayatan, Felor; Farhadi, Hadi (Applied Family Therapy Journal (AFTJ), 2024)
Objective: The present study aimed to compare the effectiveness of a combined package of Resilient Dialectical Behavior Therapy and Dialectical Behavior Therapy on the sense of coherence and marital interactions in women with marital burnout. Methods: The present study was a quasi-experimental design with a pre-test, post-test, and follow-up with a control group. The statistical population included all women aged 25 to 50 years with marital burnout who responded to the call posted in cultural centers in the city of Isfahan in the spring of 2022 and were contacted and received a moderate score based on the marital burnout questionnaire. A total of 45 individuals from the mentioned population were selected purposefully and randomly assigned to two experimental groups and one control group (15 individuals each). The experimental groups underwent nine 60-minute sessions of the combined package of Resilient Dialectical Behavior Therapy and Dialectical Behavior Therapy, while the control group received no treatment during this period. Data were collected using Antonovsky’s Sense of Coherence Questionnaire (1993) and Gottman’s Marital Interactions Questionnaire (1999) and analyzed using repeated measures ANOVA and Bonferroni post hoc test, with SPSS version 23. Findings: The results showed that both interventions significantly affected the sense of coherence and marital interactions in women with marital burnout (p < 0.05). However, in terms of the effectiveness of the two therapeutic methods, the combined package of Resilient Dialectical Behavior Therapy was more effective (p < 0.05). Conclusion: The results indicated that the combined package of Resilient Dialectical Behavior Therapy could be utilized to enhance the sense of coherence and marital interactions.